The Influence Of Delivery Speed And Timeliness On Customer Satisfaction On The Transportation Services Of Cv. Perdana Express Rantau Prapat - Tanjung, Masrina; Ayla, Sri; Rusdi, M. (JURNAL MANAJEMEN PENDIDIKAN, 2025)
The aim of this study is to ascertain whether customer satisfaction with the CV is significantly impacted by the speed at which customer goods are delivered and whether they arrive at the destination on time. Transportation services offered by Perdana Express. Quantitative methodologies are used in the study. Interviews and observation are the methods utilized to get data. In this study, 82 respondents/customers made up the sample. Simple random sample with a 5% significance level is the method used for sampling. Utilizing statistical methods and SPSS, the data analysis approach examines the validity and reliability of surveys and performs multiple linear regression analysis using the T and F tests to support the hypothesis. Research findings indicate that the timeliness variable has a close/significant impact on customer satisfaction (Y) in CV transportation services, while the delivery speed variable has a close/significant impact on customer satisfaction. At Perdana Express Rantauprapat, delivery timeliness and speed account for 98.3% of the total, with other variables and factors influencing the remaining 1.7%.Keywords: Delivery speed, timeliness, customer satisfaction.